2011
DOI: 10.1038/sc.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

The Rick Hansen Spinal Cord Injury Registry (RHSCIR): a national patient-registry

Abstract: Study design: Development of a prospective patient registry. Objective: To develop a patient registry for persons with traumatic spinal cord injuries (SCI), which can be used to answer research questions and improve patient outcomes. Setting: Nine provinces in Canada. Methods: The Rick Hansen Spinal Cord Injury Registry (RHSCIR) is part of the Translational Research Program of the Rick Hansen Institute. The launch of RHSCIR in 2004 heralded the initiation of the first nation-wide SCI patient registry within Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 11 publications
2
131
0
Order By: Relevance
“…Lesion level was determined based on the assessment made at the time of rehabilitation admission by the treating specialist. The accuracy of the SCI lesion level extraction in this study was verified using data from the Rick Hansen SCI Registry (RHSCIR), 6 which has prospective data capture of TSCI patients. 5 Of the 203 patients with an SCI that we identified, 56 were matched to their RHSCIR data record.…”
Section: Methodsmentioning
confidence: 99%
“…Lesion level was determined based on the assessment made at the time of rehabilitation admission by the treating specialist. The accuracy of the SCI lesion level extraction in this study was verified using data from the Rick Hansen SCI Registry (RHSCIR), 6 which has prospective data capture of TSCI patients. 5 Of the 203 patients with an SCI that we identified, 56 were matched to their RHSCIR data record.…”
Section: Methodsmentioning
confidence: 99%
“…23 This registry collects demographic data and the characteristics of an individual's pain after SCI over time, using elements of the SCI Pain Basic Dataset, to improve clinical care and outcomes. 23 Web-based and in-person clinical resources Both web-based and in-person clinical resources were identified to help clinicians and those with SCI manage pain. Web-based resources identified include the SCI Pain Navigator 24 and SCI-U.…”
Section: Practice Landscapementioning
confidence: 99%
“…1 The first version of the International SCI Core Data Set 1 has been the adopted standard for collecting and reporting minimal data on study population characteristics and has demonstrated its applicability globally. [2][3][4][5][6][7][8][9] All International SCI Data Sets are scheduled to undergo periodic review and revision when new knowledge and experience is gained to ensure continued relevance, acceptance and usage by the SCI clinical and research community. 10 The revisions agreed upon by consensus are summarized in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…
, PW New 4,5,6 , V Noonan 7 , MWM Post 8,9 and L Vogel 10,11Study design: The study design includes expert opinion, feedback, revisions and final consensus. Objectives: The objective of the study was to present the new knowledge obtained since the International Spinal Cord Injury (SCI) Core Data Set (Version 1.0) published in 2006, and describe the adjustments made in Version 2.0, including standardization of data reporting.
…”
mentioning
confidence: 99%